Precise and quick detection of ascorbic acid and eugenol in fruits, pharmaceuticals and medicinal herbs using hydroxyapatite-titanium dioxide nanocomposite-based electrode. (15th July 2022) - Veerapandi, G.; Meenakshi, S.; Anitta, S.; Arul, C.; Ashokkumar, P.; Sekar, C.
Highlights: Catalytic activity of Hydroxyapatite was greatly enhanced by adding TiO2 NPs. Simultaneous sensing of Ascorbic acid and Eugenol was realized in HAP-TiO2 /GCE. The sensor exhibited the LODs of 63.3 nM for AA and 94 nM for EUG. Practical application was tested in tablet, lemon, clove oil and herbal medicine. Degradation of AA was demonstrated in plant extract used for immunity boosting. Abstract: Ascorbic acid (AA) and eugenol (EUG) are well-known antioxidants found in several fruits, spices and herbs. In particular, the EUG, one of the major phytocompounds present in clove, acts as pro-oxidant or anti-oxidant depending on its concentration. Considering the medical importance of AA and EUG and its extensive usage in the form of food and medicine, we have developed a voltammetric sensor based on hydroxyapatite-TiO2 composite modified GCE for their selective and simultaneous determination over very wide linear range of 2.78–2490 µM for AA and 1.4–78 µM for EUG with the LODs of 63.3 nM and 94 nM respectively. Practical applicability of the prepared electrode has been demonstrated by detecting AA and EUG in lemon juice, vitamin tablet, clove oil and Kabasura Kudineer, an herbal decoction used as an immunity booster against number of diseases including Covid-19. The proposed HAP-TiO2 /GCE shall be useful for food and pharmaceutical industries.